DISEÑO DE UN SISTEMA CONTABLE EN EL TALLER DE SERVICIOS AUTOMOTRIZ IMPORT-FRENOS DE LA CIUDAD DE LOJA, EN EL PERIODO ENERO - JUNIO DEL 2015 - Jiménez Jiménez, Sara Sonia (2016)
The thesis is a "ACCOUNTING SYSTEM DESIGN OF A WORKSHOP ON SERVICES AUTOMOTIVE IMPORT-BRAKES Loja, in the period January - June 2015," the same as was done prior to choose the title Engineer Accounting and Auditing, Certified Public Auditor. To fulfill the initial objectives of the plan and manual accounts with their respective coding according to the movements made by the company in order to recognize each of the accounts at the time of accounting practices was developed. Then the accounting process was developed through the system has multiple documents and information provided by the owner the initial inventory was made in physical form, stating the products available for sale and thus could know the assets and liabilities has to perform its initial situation and know their heritage and could prepare the memorandum allowing operations to record every transaction in the Daybook, when completed was the majorization, the Balance, and Worksheet the income Statement, the Balance Sheet and the cash flow statement is presented, and the final result Import-brakes made a profit in the year during the set period. Auxiliary records of purchases and sales information of each of the invoices provided by the owner was designed, this helped to keep accurate records of the goods and at the same time simplified and facilitated the recording of transactions in the journal. And finally the most important financial indicators was applied to measure the ability of the company in meeting its obligations or short-term debt, finally the conclusions and recommendations aimed at giving direction to